Microwave-assisted one pot synthesis of β-cyclodextrin modified biochar for concurrent removal of Pb(II) and bisphenol a in water. (15th December 2020) - Qu, Jianhua; Dong, Min; Wei, Shuqi; Meng, Qingjuan; Hu, Limin; Hu, Qi; Wang, Lei; Han, Wei; Zhang, Ying
Highlights: β-CD functionalized biochar was fast and simply prepared under microwave irradiation. Pb(II) and BPA could be synchronously adsorbed onto BCMW -β-CD without competition. β-CD cavities were responsible for encapsulating BPA through host-guest interactions. Complexation and electrostatic attraction enhanced the Pb(II) binding onto BCMW -β-CD. Pb(II) and BPA were recovered in succession and BCMW -β-CD was effectively recycled. Abstract: Herein, β–cyclodextrin (β–CD) functionalized rice husk-derived biochar (BC) was conveniently and fast synthesized via microwave (MW)-assisted one pot process, and employed for simultaneous elimination of bisphenol A (BPA) and plumbum (Pb). Profiting by microwave irradiation, the surface modification was implemented in 15 min and the prepared BCMW -β-CD presented an excellent adsorption performance with a heterogeneous adsorption capacity of 209.20 mg/g for BPA and a theoretical monolayer uptake of 240.13 mg/g for Pb(II) in the mono-component system. Furthermore, the BCMW -β-CD could simultaneously achieve efficient cleanup of BPA and Pb(II) through avoiding the competitive behaviors between them, which were due to the different adsorption mechanisms for Pb(II) (i.e. electrostatic attraction and complexation) and BPA (i.e. host-guest supramolecular and π-π interactions). Moreover, the adsorbed BPA and Pb(II) could be sequentially desorbed with mild decrease in the adsorption performance of BCMW -β-CD even after five cycles in the Pb(II)-BPA multi-component system.